The arginine transporter Can1 negatively regulates biofilm formation in yeasts - Nishimura, Akira; Tanahashi, Ryoya; Nakagami, Kazuki; Morioka, Yuto; Takagi, Hiroshi (Frontiers in Microbiology, 2024)
The arginine transporter Can1 is a multifunctional protein of the conventional yeast Saccharomyces cerevisiae. Apart from facilitating arginine uptake, Can1 plays a pivotal role in regulating proline metabolism and maintaining cellular redox balance. Here, we report a novel function of Can1 in the control of yeast biofilm formation. First, the S. cerevisiae CAN1 gene knockout strain displayed a significant growth delay compared to the wild-type strain. Our genetic screening revealed that the slow growth of the CAN1 knockout strain is rescued by a functional deficiency of the FLO8 gene, which encodes the master transcription factor associated with biofilm formation, indicating that Can1 is involved in biofilm formation. Intriguingly, the CAN1 knockout strain promoted the Flo11-dependent aggregation, leading to higher biofilm formation. Furthermore, the CAN1 knockout strain of the pathogenic yeast Candida glabrata exhibited slower growth and higher biofilm formation, similar to S. cerevisiae. More importantly, the C. glabrata CAN1 gene knockout strain showed severe toxicity to macrophage-like cells and nematodes. The present results could help to elucidate both the molecular mechanism underlying yeast biofilm formation and the role it plays. Future investigations may offer insights that contribute to development of antibiofilm agents.